Pengaruh Pertumbuhan Penjualan, Likuiditas dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan Sektor Industri di BEI - Riadani, Ahmad Riki; Hariyanto, Eko; Fitriati, Azmi; Santoso, Slamet Eko Budi (Universitas Negeri Padang, 2024)
This study objectives to determine the effect of sales growth, liquidity and company size on profitability. The population in this study were industrial sector companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique in this study used purposive sampling technique with 108 data observed. The data analysis technique uses multiple linear regression analysis, t test, f test and coefficient of determination test using SPSS data processor. Based on the results of hypothesis testing, sales growth and liquidity variables simultaneously have a positive and significant effect on profitability. While the company size variable partially has a positive and insignificant effect on profitability